Randamoozham രണ്ടാമൂഴം - M.T. Vasudevan Nair [വാസുദേവന്‍ നായര്‍.എം.ടി] (Current Books1984, 1984)
Randamoozham is the masterpiece of Jnanpith winning writer M. T. Vasudevan Nair. It was translated into English as Second Turn in 1997. M. T. Vasudevan Nair won Vayalar Award, given for the best literary work in Malayalam, for the novel in 1985. Later, in the year 1995, Mr. Nair was awarded the highest literary award in India, Jnanpith Award, for his overall contribution to Malayalam literature. The novel is set as a retelling of the Indian epic Mahabharata, from the view of Bhima, the second Pandava.